A review of complementary therapies with medicinal plants for chemotherapy-induced peripheral neuropathy. (February 2019) - Wu, Bei-Yu; Liu, Chun-Ting; Su, Yu-Li; Chen, Shih-Yu; Chen, Yung-Hsiang; Tsai, Ming-Yen
Highlights: Chemotherapy-induced peripheral neuropathy (CIPN) is a progressive, prolonged, and often irreversible side effect of many chemotherapeutic agents. Medicinal plants are considered to be the most common complementary therapy modalities for CIPN. Therefore, we identified ten medicinal herbal extracts as well as their phytochemicals, and three herbal formulas. Multiple complementary therapies have been used and studied for decades, and their effects against CIPN are focus on anti-oxidative activity. Novel therapies or drugs that have proven to be effective in animals require further investigation, so confirmation of their efficacy and safety will require time. Abstract: Introduction: Chemotherapy-induced peripheral neuropathy (CIPN) is a progressive, prolonged, and often irreversible side effect of many chemotherapeutic agents. The development of neuropathic pain is still poorly managed by clinically available drugs at present. Methods: In this mini-review, we summarized the current knowledge of pathobiology for CIPN, and selected evidence on the application of complementary therapies in experimental studies. Results: Medicinal plants are considered to be the most common complementary therapy modalities for CIPN. Therefore, we identified ten medicinal herbal extracts as well as their phytochemicals, and three herbal formulas. Multiple complementary therapies have been used and studied for decades, and their effects against CIPN are focus on anti-oxidative activity. However, there is still controversial due to the diverse manifestations of different antineoplastic agents and complex drug interactions. Conclusions: Novel therapies or drugs that have proven to be effective in animals require further investigation, so confirmation of their efficacy and safety will require time.